PENERAPAN METODE LEAN MANUFACTURING UNTUK MEREDUKSI WASTE PRODUKSI PAKAIAN PADA UKM LARIXA - Phangestu, Bryankim; Ahmad; Saryatmo, Mohammad Agung (Jurnal Mitra Teknik Industri, 2023)
UKM Larixa is a small and medium enterprise that produces women's clothing. The production system implemented by UKM Larixa is considered to still have deficiencies, namely product defects and waste. Examples of waste that often occur are waste of waiting, waste of defects and waste of inventory. One way that can be used to reduce waste is to implement lean manufacturing. The data obtained has fulfilled the data adequacy test requirements, reliability tests and normality tests. Standard time is used as the basis for making current value stream mapping and process activity mapping where the process time lasts 1,102 minutes with a process cycle efficiency of 70.46%. The three biggest wastes after analysis are waste waiting with a percentage of 19.82%, waste inventory with a percentage of 18.86% and waste transportation with a percentage of 16.98%. Proposed improvements in order to minimize waste include labeling the final product warehouse area, adding work facilities, implementing 5S, joint cleaning programs, briefings and making SOP.